2018
DOI: 10.3389/fpls.2018.00520
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Mapping of Seedling and Adult Plant Resistance to Barley Stripe Rust (Puccinia striiformis f. sp. hordei) in India

Abstract: Barley stripe rust is caused by Puccinia striiformis f.sp. hordei, (Psh), occurs worldwide, and is a major disease in South Asia. The aim of this work was to identify and estimate effects of loci underlying quantitative resistance to rust at seedling and adult plant stages. HI-AM panel of 261 barley genotypes consisting of released cultivars from North and South America, Europe, Australia, advanced breeding lines, and local landraces from ICARDA barley program were screened at seedling and adult plant stages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…Out of the 15 QTL for SB resistance at SRT for isolate ICSB3, four were coincident with prior reports and those QTL were identified at both SRT and APS stages using different germplasm and different isolates (Zhou and Steffenson, 2013;Afanasenko et al, 2015;Gutierrez et al, 2015;Bykova et al, 2017;Wang et al, 2017). Furthermore, the QTL SRT-ICSB-12 overlaps with a QTL detected in the same panel for stripe rust and reported in Visioni et al (2018). Within the 9 QTL identified for isolate SB54, SRT-SB54-6 was already reported in a previous studies (chromosome 4H 104 cM) using different isolates and genotypes with different genetic background (Tamang et al, 2015), while QTL SRT-SB54-65 and SRT-SB54-8 were already reported for stripe rust in the same panel (Visioni et al, 2018).…”
Section: Known Co-segregating Loci and Candidate Genes For Resistancesupporting
confidence: 83%
See 4 more Smart Citations
“…Out of the 15 QTL for SB resistance at SRT for isolate ICSB3, four were coincident with prior reports and those QTL were identified at both SRT and APS stages using different germplasm and different isolates (Zhou and Steffenson, 2013;Afanasenko et al, 2015;Gutierrez et al, 2015;Bykova et al, 2017;Wang et al, 2017). Furthermore, the QTL SRT-ICSB-12 overlaps with a QTL detected in the same panel for stripe rust and reported in Visioni et al (2018). Within the 9 QTL identified for isolate SB54, SRT-SB54-6 was already reported in a previous studies (chromosome 4H 104 cM) using different isolates and genotypes with different genetic background (Tamang et al, 2015), while QTL SRT-SB54-65 and SRT-SB54-8 were already reported for stripe rust in the same panel (Visioni et al, 2018).…”
Section: Known Co-segregating Loci and Candidate Genes For Resistancesupporting
confidence: 83%
“…The extent of LD was estimated by non-linear regression analysis on the basis of intra chromosomal r 2 values (Hill and Weir, 1988;Remington et al, 2001) using nlstools package for R Statistical Software (The R Development Core Team). More information regarding genotyping population structure and LD analysis was reported by Visioni et al (2018).…”
Section: Genotyping Population Structure and Linkage Disequilibriummentioning
confidence: 99%
See 3 more Smart Citations